Marine Fungus - Baltar, Federico (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Most of the available studies on marine fungi are based on the isolation and identification of fungi from different surfaces (e.g., submerged wood, sediments, macrophytes), mostly in coastal benthic environments. However, recent evidence suggests that fungi are also present in the oceanic water column, most likely mainly associated to particles, with the genomic potential to significantly contribute to marine biogeochemical cycles. Still, we lack even basic information on the ecology of the oceanic mycobiome, precluding us from determining the ecological role of this enigmatic kingdom in our oceans. The aim of this book and Special Issue was to focus on the ecology of marine fungi. Topics include, fungal abundance, distribution, activity, and phylogenetic and/or functional diversity in coastal to open ocean environments, including seawater column and sediments, derived both from laboratory and field studies.